2000
DOI: 10.1142/s0217984900001014
|View full text |Cite
|
Sign up to set email alerts
|

ANOMALOUS TEMPERATURE EFFECT ON POINT-CONTACT Ag–LaBa2Cu3O7-x CONDUCTANCE SPECTRA

Abstract: The observation of an anomalous temperature behavior of the differential conductance versus voltage curves in contacts formed by an Ag tip and a bulk ceramic LaBa 2 Cu 3 O 7−x with Tc around 92 K is reported. For a wide range of temperatures from Tc to heliumliquid ones, we have found a crossover from curves typical for a pure conducting normal metal-superconductor interface up to Giaever tunneling characteristics with gap features shifted to high biases. We take into account the existence of a degraded interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In our previous paper [3] we presented tunneling measurements on hightemperature superconducting cuprates, another family of perovskites. It was shown that in these materials interactions of tunneling electrons with excitations inside the transitional insulating layer strongly influence the conductance spectra.…”
Section: Received February 11 2002mentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous paper [3] we presented tunneling measurements on hightemperature superconducting cuprates, another family of perovskites. It was shown that in these materials interactions of tunneling electrons with excitations inside the transitional insulating layer strongly influence the conductance spectra.…”
Section: Received February 11 2002mentioning
confidence: 99%
“…It was shown that in these materials interactions of tunneling electrons with excitations inside the transitional insulating layer strongly influence the conductance spectra. The system investigated experimentally [3] was a point-contact junction prepared with a sharp Ag tip pressed into the surface of a ceramic superconductor LaBa 2 Cu 3 O 7-x (LBCO). The latter one is known to be one of the most unstable materials among superconducting high-T c cuprates, with a bad degraded layer adjoining the surface.…”
Section: Received February 11 2002mentioning
confidence: 99%
See 1 more Smart Citation